Answer:
[tex](-2,\, 4)[/tex].
Step-by-step explanation:
To find the vertex of this parabola, start by rewriting it in the vertex form [tex]f(x) = a\, (x - h)^2 + k[/tex].
Start with the original expression:
[tex]f(x) = (x + 2)^2 + 4[/tex].
Note that in the vertex form, the sign in front of [tex]h[/tex] should be a minus. However, in [tex]f(x) = (x + 2)^2 + 4[/tex], the sign in front of [tex]2[/tex] is a plus. Since adding
[tex]f(x) = (x - (-2))^2 + 4[/tex].
Therefore:
Hence, [tex](-2,\, 4)[/tex] is the vertex of this parabola.